Contemporary advertising - Arens, William F.; Weigold, Michael F. ; Arens, Christian (New York, 2008)
Contemporary Advertising' looks at the evolution of advertising, the scope of advertising, gathering information for advertising planning, planning media strategy, using print media, and much more
Keywords: Advertising